X-ray imaging: Perovskites target X-ray detection - Heiß, Wolfgang; Brabec, Christoph (Nature Photonics, 2016)
Single crystals of perovskites are currently of interest to help fathom fundamental physical parameters limiting the performance of perovskite-based polycrystalline solar cells. Now, such perovskites offer a technology platform for optoelectronic devices, such as cheap and sensitive X-ray detectors.
Keywords: Sensors and biosensors; X-rays